The Effect of Internal Control, Compensation Appropriateness, and Organisational Ethical Culture on Accounting Fraud at PT Mahkota Global Perkasa - Adelia Gita Cahyani; Lili Syafitri; Aris Munandar (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyze the effect of internal control, appropriateness of compensation and organizational ethical culture on accounting fraud at PT Mahkota Global Perkasa, Bukit Kecil sub-district, Palembang city, South Sumatra. The objects in this study were all 42 employees of PT Mahkota Global Perkasa. The analysis technique used is multiple linear analysis which is processed using the help of the Statistical Product and Service Solution (SPSS) computer program version 26. Based on the results of the research and the hypothesis shows that there is an effect of internal control, appropriateness of compensation, and organizational ethical culture on accounting fraud at PT Mahkota Global Perkasa